Turkey Economic Monitor, December 2018 : Steadying the Ship - World Bank Group (World Bank, Washington, DC, 2019)
Mid-2018 was a period of intense market volatility and rising economic stress in Turkey that was precipitated by existing macroeconomic imbalances and elevated political tensions with the United Staes. A confluence of burgeoning domestic economic imbalances and a more challenging external environmentled to a dent in investor confidence in Turkish assets and a sharp slowdown in capital flows to Turkey in 2018 Q2-Q3. Though this did not technically amount to a sudden stop, Turkey was particularly badly affected by a general move away from emerging markets (EMDE) due to its accumulated macro imbalances (high current account deficit, high inflation, overheating economy) and perceived policy weaknesses. Market volatility in Turkey has subsided since the turbulence in August, but the economic situation remains fragile. Turkey’s large external exposure leaves it vulnerable to further market jitters and external monetary tightening. The external shock in the summer of 2018 also translated into significant real sector impacts, including a sharp acceleration in inflation from already elevated levels. The gap between consumer and producer price inflation widened significantly since July, reflecting suppliers’ inability to pass on priceincreases to consumers due to declining demand. High production costs together with slowing demand have prompted supply side adjustments.